What Makes Inquiry Stick? The Quality of Preservice Teachers’ Understanding of Inquiry - Mark W. Aulls; Diana Tabatabai; Bruce M. Shore (SAGE Open, 2016)
This nonexperimental, exploratory, mixed-design study used questionnaires with 167 preservice secondary teachers to identify prior educational experiences associated with student-teachers’ inquiry understanding. Understanding was determined through content analysis then open coding of definitions of inquiry and descriptions of best-experienced inquiry instruction, in terms of 23 potential learner-inquiry outcomes. Only two of seven educational-context variables related to understanding: prior experience doing a thesis or research—especially to definition quality and having taken a research-methods course—especially to description quality. How definitions and descriptions of inquiry are different and similar was analyzed qualitatively and quantitatively. Implications for methodology, theory, and practice were presented, for example, research opportunities and research-methods training during teacher education.